Assessment of the epizootic situation by invasive diseases in reindeer farms in the Murmansk Oblast - E. V. Firsova; R. A. Pochepko (Ветеринария сегодня)
Reindeer invasive diseases causes ignificant damage to reindeer farms due to reduction in animal productivity and deterioration in quality of reindeer products. Helminthiases take a special place among them. Knowledge of the epizootic situation will contribute to the successful organization of a system of therapeutic and preventive measures to protect the domestic reindeer stock from helminthiases. The article presents assessment results for the invasive disease epizootic situation in reindeer farms in the Murmansk Oblast in 2018–2021. The research was carried out in two large reindeer farms – APC “Tundra” and APC HFESEN “Olenevod” during the planned slaughter of reindeer. A totalof 4,048 deer carcasses of all ages were examined and 199 samples of faeces were tested. A retrospective analysis of the veterinary service’s data showed that, among helminthiases, mainly cysticercosis is recorded in reindeer herds of the Murmansk Oblast. The prevalence of cestodes infection variesfrom 0.16 to 0.83% depending on the year, however the extensiveness of cysticercosis invasion of reindeer is decreasing. The prevalence of oedemagenosis varied in different age and sex groups from 25 to 100%. It was found that reindeer of all ages were infested with paramphistomiasis (12.50–15.15%), setariasis (5.36–6.06%), nematodiasis (3.0–6.0%), dictyocaulosis (3.03–3.57%), protostrongylosis (3,0%) and, to the least extent, echinococcosis (0.04%). Helminths of the genus Taenia, class Cestoda, that cause cysticercosis, mainly infest young animals – extensiveness of invasion (EI) is 0.50–0.81%. Thus, oedemagenosis and paramphistomiasis prevail in the structure of helminth infections; they are recorded in all reindeer herds. It was established that invasive diseases occur in the form of mixed invasions. Mixed invasions most often occur in the following associations: oedemagenosis + protostrongylosis, oedemagenosis + paramphistomiasis + setariasis, oedemagenosis + paramphistomiasis + cysticercosis (finnosis), oedemagenosis + dictyocaulosis + protostrongylosis.